Le conclusioni della filosofia del conoscere Appunti sul programma “razionalista” di Husserl e Bontadini - De Santis, Daniele (Bollettino Filosofico, 2018)
The present paper wants to offer neither a Husserlian reading of Gustavo Bontadini, nor a “Bontadinian” interpretation of Husserl’s transcendental phenomenology. My aim is more circumscribed, and yet systematic: it consists in providing an examination of both Husserl’s and Bontadini’s interpretation of the history of modern philosophy from Descartes to Kant, in order to bring to the fore analogies and differences between the two. As I will show, Husserl’s reading of the history of modern philosophy is based on a twofold notion of rationality, or, rather, he distinguishes, quite accurately, two concepts of rationality - whose struggle animates and characterizes, from within, the philosophical trajectory of modernity.